2015
DOI: 10.2298/abs140917043g
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the causes of lower gastrointestinal bleeding in a children’s hospital in northeastern Romania

Abstract: The aims of this five-year retrospective study was to investigate the common etiologies, clinical, biological and pathological patterns of lower gastrointestinal bleeding in children from a hospital center in northeastern Romania. We included in the study 118 children with lower gastrointestinal hemorrhage or two consecutive positive fecal occult blood tests. Patients were divided into three age groups (0-2 years, 3-10 years, 11-18 years) and the findings were reported separately for each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…A previous study showed that H. pylori infection accounted for 6% of children with duodenitis[8]. Moreover, Gimiga et al[9] found that gastritis and duodenitis contributed to half of children with upper gastrointestinal bleeding, and 36.89% of participants were diagnosed with H. pylori infection. These findings suggested a relatively high prevalence of children with H. pylori infection in the digestive system.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that H. pylori infection accounted for 6% of children with duodenitis[8]. Moreover, Gimiga et al[9] found that gastritis and duodenitis contributed to half of children with upper gastrointestinal bleeding, and 36.89% of participants were diagnosed with H. pylori infection. These findings suggested a relatively high prevalence of children with H. pylori infection in the digestive system.…”
Section: Introductionmentioning
confidence: 99%
“…GIE can reveal the underlying etiology of GIB in most cases[ 3 ]. However, it requires the experience and coordination of the medical team to provide specialized patient care[ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent sources of hematemesis are varices and mucosal gastric and duodenal lesions, often caused by drug ingestion [1]. Moreover, a Romanian study performed on 103 children discovered that the most frequent cause of upper gastrointestinal bleeding was erosive gastritis, which accounted for a third of all cases [2]. According to Deerojanawong et al (2019) gastrointestinal bleeding is not uncommon among intensive care patients [3], with mechanically ventilated children being at risk of developing gastrointestinal hemorrhage [4].…”
Section: Introductionmentioning
confidence: 99%
“…In children, inadequate nutrition and drugs are cited as more common etiological factors [2,5], compared to adults, where gastrointestinal tumors represent a major cause of digestive bleedings.…”
Section: Introductionmentioning
confidence: 99%